2016
DOI: 10.1016/j.jevs.2016.02.228
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Omeprazole and a Dietary Supplement for the Management of Squamous Gastric Ulceration in Horses

Abstract: Although several studies have assessed the short-term effect of dietary supplements on the treatment and prevention of gastric ulceration in horses, few have assessed the response over a duration of more than 30 days. 2A blinded randomised non-inferiority clinical trial was conducted using forty-two Thoroughbred horses in race training with squamous ulceration of ≥ grade 2/4, randomly assigned to one of two treatment groups for a period of 90 days: omeprazole at the full label dose of 4mg/kg or the Succeed® di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Kerbyson et al demonstrated ulcer healing (grade <1/4) in 52% of Thoroughbred racehorses following 4 weeks of treatment with 4mg/kg buffered omeprazole paste where horses raced as normal, with five-day withdrawal periods observed prior to each race. 104 This is lower than published figures following treatment with an uninterrupted course but may be more representative of use in clinical practice.…”
Section: Treatment and Managementmentioning
confidence: 70%
See 1 more Smart Citation
“…Kerbyson et al demonstrated ulcer healing (grade <1/4) in 52% of Thoroughbred racehorses following 4 weeks of treatment with 4mg/kg buffered omeprazole paste where horses raced as normal, with five-day withdrawal periods observed prior to each race. 104 This is lower than published figures following treatment with an uninterrupted course but may be more representative of use in clinical practice.…”
Section: Treatment and Managementmentioning
confidence: 70%
“…A supplement containing beta glucan, saccharomyces yeast and amino acids (Succeed digestive conditioning ® ) was inferior to omeprazole when compared over a 30-day period in racehorses in training but when examined over a 90-day period, was found to be non-inferior to omeprazole. 104 A similar supplement containing herbs, polysaccharides, amino acids, antioxidants and probiotics (Smart Gut Ultra Pellet ® ) prevented the number of squamous ulcers from increasing in intermittently fed stabled horses following omeprazole treatment when compared to untreated controls. 78 Porcine hydrolyzed collagen enhanced the effects of omeprazole on gastric pH, inhibited gastrin secretion after feeding and resulted in fewer squamous ulcers after long term (56 days) in stall-confined horses undergoing omeprazole treatment and feed-deprivation.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Further, omeprazole has been shown to induce its own metabolism in humans and, consistent with this, omeprazole has shown to have a reduced area under the curve (AUC) and maximal concentration (Cmax) on day 29 of treatment when compared to day 1 in horses [ 212 ]. Another study showed a decreased efficacy for ESGD prevention in horses treated for 90 days [ 213 ]. Therefore, the long-term use of omeprazole to prevent ESGD is not recommended without the significant application of other management factor alterations first and appropriate monitoring.…”
Section: Preventionmentioning
confidence: 99%
“…When complete healing was assessed the percentage of responders dropped from 28.8% at 30 days, to 19% and 10.6% at 60 and 90 days, respectively (Kerbyson et al . 2016). To the author’s knowledge, there are no peer‐reviewed studies to support the use of long‐term omeprazole therapy for the prevention of equine glandular gastric disease (EGGD).…”
Section: Upregulation Of Omeprazole Metabolism and Decreased Efficacy Over Timementioning
confidence: 99%